Thymoma associated with systemic lupus erythematosus: a case report - Arribasplata-Purizaca, Kattia (2021)
A 30-year-old woman with a previous diagnosis of systemic lupus erythematosus presented with fever, night sweats, mild dyspnea, epigastric pain, and weight loss. The tomography showed a mediastinal mass. The pathology and immunohistochemistry of the tumor was compatible with a B1 thymoma. Even the low frequency among SLE patients, we must include thymoma in every patient with SLE and a mediastinal mass.